A Compensation Method for Relative Movement Between A Sensor Array and the Abdomen for Magnetic Localization of Capsule Endoscopes - Zeising, Samuel; Schneider, Alexander; Thalmayer, Angelika; Fischer, Georg; Kirchner, Jens (IEEE Transactions on Instrumentation and Measurement, 2022)

A Robust and Real-Time Capable Envelope-Based Algorithm for Heart Sound Classification: Validation under Different Physiological Conditions - Thalmayer, Angelika; Zeising, Samuel; Fischer, Georg; Kirchner, Jens (Sensors, 2020)
This paper proposes a robust and real-time capable algorithm for classification of the first and second heart sounds. The classification algorithm is based on the evaluation of the envelope curve of the phonocardiogram. For the evaluation, in contrast to other studies, measurements on twelve probands were conducted in different physiological conditions. Moreover, for each measurement the auscultation point, posture and physical stress were varied. The proposed envelope-based algorithm is tested with two different methods for envelope curve extraction: the Hilbert transform and the short-time Fourier transform. The performance of the classification of the first heart sounds is evaluated by using a reference electrocardiogram. Overall, by using the Hilbert transform, the algorithm has a better performance regarding the F1-score and computational effort. The proposed algorithm achieves for the S1 classification an F1-score up to 95.7% and in average 90.5 %. The algorithm is robust against the age, BMI, posture, heart rate and auscultation point (except measurements on the back) of the subjects. The ECG and PCG records are available from the authors.<br

A Simple and Low-Cost Technique to Measure the Magnetic Susceptibility of Ferrofluids - Thalmayer, Angelika; Xiao, Keyu; Lübke, Maximilian; Borin, Dmitry; Odenbach, Stefan; Unterweger, Harald; Helmreich, Klaus; Fischer, Georg (IEEE Sensors, 2023)

Commercial and Scientific Solutions for Blood Glucose Monitoring—A Review - Xue, Yirui; Thalmayer, Angelika; Zeising, Samuel; Fischer, Georg; Lübke, Maximilian (Sensors, 2022)

Differential Geomagnetic Compensation Method for the Static Magnetic Localization of Capsule Endoscopes During Activities of the Daily Life - Zeising, Samuel; Thalmayer, Angelika; Fischer, Georg; Kirchner, Jens (IEEE Transactions on Instrumentation and Measurement, 2021)

Evaluation of the Impact of Static Interference on an Empirical Data Based Static Magnetic Localization Setup for Capsule Endoscopy - Zeising, Samuel; Anzai, Daisuke; Thalmayer, Angelika; Fischer, Georg; Kirchner, Jens (Current Directions in Biomedical Engineering, 2020)

Experimental and Numerical Modeling of Magnetic Drug Targeting: Can We Trust Particle-Based Models? - Thalmayer, Angelika; Xiao, Keyu; Wolff, Paul; Fischer, Georg (IEEE Journal on Multiscale and Multiphysics Computational Techniques, 2025)

Experimental and Simulative Analysis of Magnetic Nanoparticle Accumulation Using Various Halbach Arrays - Thalmayer, Angelika; Götz, Kilian; Lübke, Maximilian; Fischer, Georg (Current Directions in Biomedical Engineering, 2024)

Experimental and Simulative Characterization of a Hybrid Magnetic Array for Steering Superparamagnetic Nanoparticles in Drug Targeting - Thalmayer, Angelika; Fink, Lucas; Fischer, Georg (IEEE Transactions on Biomedical Engineering, 2025)

How the Magnetization Angle of a Linear Halbach Array Influences Particle Steering in Magnetic Drug Targeting – A Systematic Evaluation and Optimization - Thalmayer, Angelika; Götz, Kilian; Fischer, Georg (Symmetry, 2024)

Impact of the Array Length on Particle Attraction in Magnetic Drug Targeting – Investigation Using an Exponential Approximation of the Magnetic Field - Thalmayer, Angelika; Götz, Kilian; Zeising, Samuel; Fischer, Georg (IEEE Magnetics Letters, 2023)

Innovative Differential Magnetic Localization Method for Capsule Endoscopy to Prevent Interference Caused by the Geomagnetic Field - Zeising, Samuel; Anzai, Daisuke; Thalmayer, Angelika; Fischer, Georg; Kirchner, Jens (Advances in Radio Science : Kleinheubacher Berichte, 2021)

Innovative Hybrid Halbach Array for Steering Magnetic Nanoparticles Through a Bifurcation - Thalmayer, Angelika; Fischer, Georg (Current Directions in Biomedical Engineering, 2023)

Investigation of Particle Steering for Different Cylindrical Permanent Magnets in Magnetic Drug Targeting - Thalmayer, Angelika; Zeising, Samuel; Fischer, Georg; Kirchner, Jens (7th International Electronic Conference on Sensors and Applications, 2020)
Keywords: magnetic drug targeting; particle steering; permanent magnet

Localization of Passively Guided Capsule Endoscopes-A Review - Zeising, Samuel; Thalmayer, Angelika; Lübke, Maximilian; Fischer, Georg; Kirchner, Jens (IEEE Sensors Journal, 2022)

Low-Frequency Magnetic Localization of Capsule Endoscopes with an Integrated Coil - Zeising, Samuel; Seidl, Rebecca; Thalmayer, Angelika; Fischer, Georg; Kirchner, Jens (8th International Symposium on Sensor Science, 2021)

Particle Steering In Magnetic Drug Targeting: A Simple Comsol Model - Thalmayer, Angelika; Zeising, Samuel; Ahmed, Doaa; Fischer, Georg; Kirchner, Jens (COMSOL Conference 2020, 2020)

Performance Optimization of a Differential Method for Localization of Capsule Endoscopes - Zeising, Samuel; Ararat, Kivanc; Thalmayer, Angelika; Anzai, Daisuke; Fischer, Georg; Kirchner, Jens (7th International Electronic Conference on Sensors and Applications, 2020)

Quasi-Static Magnetic Localization of Capsule Endoscopes with an Active Integrated Coil - Zeising, Samuel; Seidl, Rebecca; Thalmayer, Angelika; Fischer, Georg; Kirchner, Jens (2021 IEEE Sensor Application Symposium, 2021)

Reduced Steering Performance in Magnetic Drug Targeting Induced by Shielding Arising from Accumulation of Particles - Thalmayer, Angelika; Zeising, Samuel; Fischer, Georg (Current Directions in Biomedical Engineering, 2022)

Reducing Dispersion in Molecular Communication by Placing Decelerators in the Propagation Channel - Thalmayer, Angelika; Ladebeck, Alisa; Zeising, Samuel; Fischer, Georg (7th Workshop on Molecular Communications, 2023)

Reducing Dispersion in Molecular Communications by Placing Decelerators in the Propagation Channel - Thalmayer, Angelika; Ladebeck, Alisa; Zeising, Samuel; Fischer, Georg (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2023)

Stability of the Frequency Spectrum of the Heart Sounds S1 and S2 under Different Physiological Conditions - Zeising, Samuel; Thalmayer, Angelika; Fischer, Georg; Kirchner, Jens (The 20th IEEE International Conference on Bioinformatics and Bioengineering, 2020)

Static Magnetic Localization of Capsule Endoscopes: A Differential Method - Zeising, Samuel; Ararat, Kivanc; Thalmayer, Angelika; Fischer, Georg; Kirchner, Jens (COMSOL Conference 2020, 2020)

Steering Magnetic Nanoparticles by Utilizing an Adjustable Linear Halbach Array - Thalmayer, Angelika (FAU-Networking Night Medizintechnik (Poster Presentation), 2021)

Steering Magnetic Nanoparticles by Utilizing an Adjustable Linear Halbach Array - Thalmayer, Angelika; Zeising, Samuel; Fischer, Georg; Kirchner, Jens (Kleinheubacher Tagung 2021, 2021)

Systematic Performance Evaluation of a Novel Optimized Differential Localization Method for Capsule Endoscopes - Zeising, Samuel; Ararat, Kivanc; Thalmayer, Angelika; Anzai, Daisuke; Fischer, Georg; Kirchner, Jens (Sensors, 2021)

Toward Magnetic Localization of Capsule Endoscopes during Daily Life Activities - Zeising, Samuel; Thalmayer, Angelika; Fischer, Georg; Kirchner, Jens (Kleinheubacher Tagung 2021, 2021)

Towards Differential Static Magnetic Localization of Commercial Capsule Endoscopes: An Evaluation Using Different Ring and Cylindrical Magnets - Zeising, Samuel; Chen, Lu; Thalmayer, Angelika; Fischer, Georg; Kirchner, Jens (Advances in Radio Science : Kleinheubacher Berichte, 2023)

Towards Realisation of a Non-Invasive Blood Glucose Sensor Using Microstripline - Zeising, Samuel; Kirchner, Jens; Fazeli Khalili, Hossein; Ahmed, Doaa; Lübke, Maximilian; Thalmayer, Angelika; Fischer, Georg (International Instrumentation and Measurement Technology Conference (I2MTC), 2020)

Towards Steering Magnetic Nanoparticles in Drug Targeting Using a Linear Halbach Array - Thalmayer, Angelika; Zeising, Samuel; Lübke, Maximilian; Fischer, Georg (Advances in Radio Science : Kleinheubacher Berichte, 2023)

Tracking the Traveled Distance of Capsule Endoscopes along a Gastrointestinal-Tract Model Using Differential Static Magnetic Localization - Zeising, Samuel; Chen, Lu; Thalmayer, Angelika; Lübke, Maximilian; Fischer, Georg; Kirchner, Jens (Diagnostics, 2022)

Utilizing the Ferromagnetic Battery of Capsule Endoscopes for Static Magnetic Localization - Zeising, Samuel; Ararat, Kivanc; Thalmayer, Angelika; Fischer, Georg; Kirchner, Jens (2021 IEEE 19th International Symposium on Antenna Technology and Applied Electromagnetics (ANTEM), 2021)